﻿68Ga-RM2 PET in PSMA- positive and -negative prostate cancer patients - Hoberück, Sebastian; Michler, Enrico; Wunderlich, Gerd; Löck, Steffen; Hölscher, Tobias; Froehner, Michael; Braune, Anja; Ivan, Platzek; Seppelt, Danilo; Zöphel, Klaus; Kotzerke, Jörg (Nuklearmedizin - NuclearMedicine, 2019)
﻿Aim 68Ga-PSMA-11 is the gold standard for molecular imaging of prostate cancer. However, recurrent tumor manifestations or metastases cannot be detected in every case. Therefore, we investigated if there is an additive value of the gastrin-releasing peptide receptor (GRP-R) ligand 68Ga-RM2 compared to the well-established 68Ga-PSMA-11 in patients with (Group 1) and without (Group 2) pathologic PSMA-expression in different tumor stages.Patients and Methods Sixteen men (median age: 74 years, range 50–80 years) with prostate cancer in different stages who had a recent negative (n = 8) or pathologic (n = 8) PSMA PET underwent a subsequent 68Ga-RM2 PET. Both examinations were analyzed qualitatively and quantitatively and compared in terms of pathologic and physiologic tracer distribution.Results None of the PSMA-negative patients showed any pathological RM2-accumulation. Pathologic PSMA-uptake was observed in 8 patients of whom 5 had pathologic RM2-uptake. The number of patients with a local recurrence was equal in both scans (n = 3). Bone metastases and lymph node metastases were detected in less patients in RM2 PET compared to PSMA PET (n = 4 vs. 7 and n = 2 vs. 5, respectively). In one patient, PSMA-positive liver metastases were not detected in RM2. RM2 PET revealed two additional lesions indicative for bone metastases in two patients with multiple PSMA-positive bone metastases, which had no therapeutic consequence.Conclusion At least in our small and heterogeneous patient population, 68Ga-RM2 showed no clinically relevant, additional benefit compared to 68Ga-PSMA-11 PET.
Keywords: PSMA; Bombesin; RM2; prostate cancer; PET